Small Cerebellopontine Angle Meningioma—Surgical Experience of 162 Patients and Literature Review - Bu, Jiyuan; Pan, Pengjie; Yao, Hui; Gong, Weiyi; Liu, Yuan; Yu, Zhengquan; Wang, Zhong; Wu, Jiang; Chen, Gang (Frontiers in Oncology, 2020)
Objective To retrospective analyze the clinical data of 162 patients with small cerebellopontine angle meningiomas. To compare with the nature of tumors, symptoms pre- and post-treatments, neurological deficit and prognosis in literatures. To explore the surgical outcomes of small cerebellopontine angle meningiomas and summarize the surgical experience. Methods All of 162 patients with small cerebellopontine angle meningiomas underwent surgery between January 2010 and December 2019 in the neurosurgery department of the First Affiliated Hospital of Soochow University. This cohort of 8 literatures reported about stereotactic radiotherapy of small cerebellopontine angle meningiomas between January 2010 and December 2019. All clinical data were obtained for analysis. Results Compared with stereotactic radiotherapy, surgical treatment for small cerebellopontine angle meningiomas lead to the better results in relieving symptoms and inhibiting tumor progression. Surgical treatment can obtain the exact pathological examination results to guide the further treatment. Conclusions Surgical treatment should be the first choice for small cerebellopontine angle meningiomas.